PEMANFAATAN KARBON AKTIF ARANG BATUBARA (KAAB) UNTUK MENURUNKAN KADAR ION LOGAM BERAT Cu2+ DAN Ag+ PADA LIMBAH CAIR INDUSTRI - Kusmiyati Kusmiyati; Puspita Adi Lystanto; Kunthi Pratiwi (Reaktor, 2012)
UTILIZATION OF CHAR COAL ACTIVATED CARBON (CCAB) FOR HEAVY IONS (Cu2+ AND Ag+) REDUCTION FROM INDUSTRIAL WASTE WATER. Industrial wastewater may contain heavy metals such as Cu and Ag those are harmful to the environment if discharged without pretreatment. One of the methods to reduce heavy metals in wastewater is adsorption, to separate certain components from liquid to the surface of solids. Adsorption is a simple method, but most of the adsorbents are expensive, therefore a cheaper adsorbent is required to reduce the cost of the adsorption process. This work utilized bottom ash as an adsorbent. Bottom ash is a waste of combustion products in the coal industry, which contain potentially harmful materials. Activation of bottom ash was made by soaking in peroxide and continuing by heating at a temperature of 500oC. This study was aimed to determine the influence of process parameters (concentration, pH and processing time) to the percentage of amount heavy metals adsorbed, to study the equation isotherm adsorption using Langmuir and Freundlich models, and to calculate the kinetic constants of adsorption based on pseudo -first- order and pseudo-second-order kinetic model. The experiment was conducted in the batch system, where 10 grams bottom ash was mixed with 400 ml of synthetic waste. AAS was used to determine the heavy metals content in the waste solution. The results showed that bottom ash can be used to reduce heavy metals of Cu2+ and Ag+, the optimum condition when the concentration of 25 ppm under acidic conditions, bottom ash was able to adsorb Cu2+ metals ion by 62.79-80.25% at pH 4, and 65.54-85.98% at neutral pH with the same adsorption time of 300 min. For the ion metals Ag+, at acidic solution the metals ion can be adsorbed by 56.51-82.21%, while at neutral pH conditions 59.92-87.55%. Adsorption of bottom ash follows the model of Freundlich isotherm adsorption at acidic and neutral condition, the correlation coefficient (R2)obtained was 0.994 for Cu2+ metals ion and 0.984 for the Ag+ metals ion at acidic solution, whereas 0.986 for Cu2+ metals ion and 9.69 for the Ag+ metals ion at neutral pH. Kinetic model of second order rate describe the adsorption process well at acidic and neutral conditions. At the optimum conditions, the correlation coefficient (R2) of 0.998 for Cu2+ and 0.999 for the Ag+ at acidic solution, whereas 0.993 for Cu2+ and 9.998 for the Ag+ at neutral pH were obtained.  Limbah cair industri bisa mengandung ion logam berat seperti Cu2+ dan Ag+ yang berbahaya bagi lingkungan jika dibuang tanpa melalui pengolahan dahulu. Metode yang digunakan untuk mengurangi ion logam berat dalam limbah cair sudah banyak dilakukan, salah satu diantaranya adalah adsorpsi, yaitu memisahkan komponen tertentu dari fluida ke permukaan zat padat. Adsorpsi merupakan metode yang mudah, akan tetapi kebanyakan adsorben yang digunakan harganya mahal, sehingga perlu adanya alternatif adsorben yang murah. Penelitian ini memanfaatkan karbon aktif arang batubara (KAAB) sebagai adsorbennya. Arang batubara merupakan limbah hasil pembakaran batubara pada industri, yang berpotensi untuk dikembangkan menjadi adsorben, sehingga dapat mengurangi pencemaran lingkungan. Pengaktifan arang batubara dilakukan dengan merendamnya dalam peroxide kemudian dilakukan pemanasan pada suhu 500°C. Penelitian ini bertujuan untuk mengetahui pengaruh parameter proses (konsentrasi, pH dan waktu proses) terhadap persentase ion logam berat teradsorpsi dalam KAAB, mempelajari persamaan kesetimbangan adsorpsi dengan menggunakan model isoterm adsorpsi Langmuir dan Freundlich, dan menghitung konstanta kinetika adsorpsi dengan pendekatan model kinetika pseudo-first-order dan pseudo-second-order. Pelaksanaan penelitian dengan batch, yaitu mengkontakkan 10 gram KAAB dengan 400 ml limbah sintetis. Pengujian kadar ion logam berat menggunakan AAS (Atomic Absorption Spectrophotometer). Hasil penelitian menunjukkan bahwa KAAB dapat digunakan untuk mengurangi kandungan ion logam berat Cu2+ dan Ag+, pada kondisi optimum saat konsentrasi 25 ppm, KAAB mampu mengadsorpsi ion logam Cu2+ sebesar 64,60-88,89% pada pH asam sedangkan pada pH netral sebesar 67,02-80,25%. Untuk ion logam Ag+ pada pH asam mampu mengadsorpsi ion logam sebesar 69,97-82,21%  sedangkan pada kondisi pH netral sebesar 72,71-87,55%. Adsorpsi KAAB mengikuti model Isoterm adsorpsi Freundlich pada pH asam dan netral, koefisien korelasi (R2) 0,994 untuk ion logam Cu2+ dan 0,984 untuk ion logam Ag+saat pH asam, sedangkan pH netral (R2) 0,986 untuk ion logam Cu2+ dan 9,69 untuk ion logam Ag+. Kinetika model second-order rate sesuai untuk proses adsorpsi pH asam dan netral, pada kondisi optimum harga koefisien korelasi (R2) >  0,998.